A comparative study of severe scorpion envenomation in children caused by Tityus bahiensis and Tityus serrulatus Estudo comparativo do envenenamento escorpiônico grave em crianças provocado por Tityus bahiensis e Tityus serrulatus - Fábio Bucaretchi; Emílio CE Baracat; Roberto J.N. Nogueira; Aniel Chaves; Flávio A.D. Zambrone; Márcia R.C.C. Fonseca; Francis S Tourinho (Revista do Instituto de Medicina Tropical de São Paulo, 1995)
From January 1984 to May 1994, 17 of 239 children under 15 years old stung by Tityus serrulatus (15.1%) or Tityus bahiensis (84.9%) presented severe envenoming. Of these 17 patients (1-11 years old; median=2 yr) 14 were stung by T.serrulatus and three by T.bahiensis. All of them received scorpion antivenom i.v. at times ranging from 45 min. to 5 h after the accident (median=2h). On admission, the main clinical manifestations and laboratory and electrocardiographic changes were: vomiting (17), diaphoresis (15), tachycardia (14), prostration (10), tachypnea (8), arterial hypertension (7), arterial hypotension (5), tremors (5), hypothermia (4), hyperglycemia (17), leukocytosis (16/16), hypokalemia (13/17), increased CK-MB enzyme activity (>6% of the total CK, 11/12), hyperamylasemia (11/14), sinusal tachycardia (16/17) and a myocardial infarction-like pattern (11/17). Six patients stung by T.serrulatus had depressed left ventricular systolic function assessed by means of echocardiography. Of these, five presented pulmonary edema and four had shock. A child aged two-years old presented severe respiratory failure and died 65 h after being stung by T.serrulatus. Severe envenomations caused by T.serrulatus were 26.2 times more frequent than those caused by T.bahiensis (p<0.001). No período de janeiro de 1984 a maio de 1994, de 239 crianças com até 15 anos de idade, picadas por escorpiões pertencentes às espécies T.bahiensis (84,9%) e T.serrulatus (15,1%), 17 apresentaram envenenamento grave. Destes 17 pacientes, cuja idade variou de 1 a 11 anos (mediana=2anos), 14 foram picados por T.serrulatus e 3 por T.bahiensis. Todos receberam anti-veneno escorpiônico i.v. entre 45 min. e 5 hs após o acidente (mediana=2 horas). À admissão, as principais manifestações clínicas, alterações laboratoriais e eletrocardiográficas observadas foram: vômitos(17), sudorese profusa(15), taquicardia(14), prostração(10), taquipnéia (8), hipertensão arterial(7), hipotensão arterial(5), tremores(5), hipotermia(4), hiperglicemia(17), ...